Utilização de um gerador de bolhas ultrafinas para oxigenação de tanques de criação de tilápia do Nilo em sistema aquapônico - Marques, Daniele Ferreira (2022)
The objective of this research was to evaluate the use of an ultrafine bubble generator for oxygenation of Nile tilapia (Oreochromis niloticus) culture tanks in an aquaponic system. The present research was carried out at the Estação de Aquicultura of the Universidade Federal do Ceará and was divided in 2 experiments: 1) water saturation test with dissolved oxygen (DO); 2) application of ultrafine bubble technology in the Nile tilapia culture in an aquaponic system. The first experiment was carried out in a 2 m³ tank. Initially the water was completely deoxygenated using sodium sulfite and cobalt chloride as a catalyst. After the DO concentration reached 0.0 mg/L, the ultrafine bubble generator system was activated and the saturation test started with the measurement of DO and temperature values once every minute for an interval of 60 minutes. The second experiment was carried out in an experimental unit composed of two independent aquaponic systems. Each aquaponic system consisted of three 2 m³ tanks, a 500 L clarifier, a 500 L biological reactor, a degassing tower, a pressurized mechanical filter and four hydroponic chutes. An ultrafine oxygen bubble generator (BUF treatment) was connected to one of the systems, while conventional aeration (AC treatment) was provided to the other. In each tank, 54 Nile tilapia were stored, with an average initial weight of approximately 60 ± 13,5 g, and about 27-30 lettuce (Lactuca sativa) seedlings were transplanted to each hydroponic chute. After starting the ultrafine bubble generator in experiment 1, it took 21 min for the OD concentration in the water to reach 7.85 mg/L (100% saturation). At the end of the 60 min test, the DO concentration reached a value of 21.8 mg/L (277.52%). Throughout the entire experimental period in experiment 2, a significant difference (p<0.05) was observed between the DO concentrations in the BUF and AC treatments. The highest DO means in both treatments were observed in the morning with 14.4 ± 3.1 mg/L for BUF and 7.5 ± 0.5 mg/L for AC. Among the zootechnical performance parameters evaluated, only the allometric condition factor showed a significant difference (p<0.05) between BUF and AC treatments, 1.19 ± 0.11 and 1.12 ± 0.10, respectively. A significant difference (p<0.05) was observed for most of the phytotechnical performance parameters of lettuce with the BUF treatment presenting higher values in almost all analyzes performed. Thus, it can be concluded that the ultrafine oxygen bubble generator: 1) was efficient in increasing the DO concentration in both experiments; 2) did not result in a significant improvement in the zootechnical performance of tilapia; and 3) resulted in a significant improvement in the phytotechnical performance of lettuce.